Coastal and estuarine fine sediment processes - McAnally, William H.; Mehta, Ashish J. (Amsterdam ; New York : Elsevier, 2001)
The INTERCOH series of conferences bring together the world's leading researchers and practitioners in cohesive sediment transport processes to share recent insights. This book presents papers that examine the spectrum of fine sediment transport related science and engineering, including the basics and applications of flocculation, settling, deposition, and erosion, advanced numerical models used in engineering practice, and applications to mud flats and harbor siltation.
Cohesive sediment transport modeling : European perspective / E.A. Toorman -- Collisional aggregation of fine estuarial sediment / W.H. McAnally and A.J. Mehta -- Erosion of a deposited layer of cohesive sediment / I. Piedra-Cueva and M. Mory -- Critical shear stress for cohesive sediment transport / K. Taki -- Mud scour on a slope under breaking waves / H. Yamanishi, O. Higashi, T. Kusuda and R. Watanabe -- Fluid mud in the wave-dominated environment revisited / Y. Li and A.J. Mehta -- Response of stratified muddy beds to water waves / R. Silva Jacinto and P. Le Hir -- Assessment of the erodibility of fine/coarse sediment mixtures / H. Torfs, J. Jiang and A.J. Mehta -- Rapid siltation from saturated mud suspensions / J.C. Winterwerp, R.E. Uittenbogaard and J.M. de Kok -- Density development during erosion of cohesive sediment / C. Johansen and T. Larsen -- Clay-silt sediment modeling using multiple grain classes, part 1. Settling and deposition / A.M. Teeter -- Clay-silt sediment modeling using multiple grain classes, part 2. Application to shallow-water resuspension and deposition / A.M. Teeter -- Analysis of nearshore cohesive sediment depositional process using fractals / Li Yan and Xia Xiaoming --Laboratory experiments on consolidation and strength of bottom mud / L.M. Merckelbach, G.C. Sills and C. Kranenburg -- A framework for cohesive sediment transport simulation for the coastal waters of Korea / D.Y. Lee, J.L. Lee, K.C. Jun and K.S. Park -- Application of the continuous modeling concept to simulate high-concentration suspended sediment in a macrotidal estuary / P. Le Hir, P. Bassoullet and H. Jestin -- Modeling of fluid mud flow on an inclined bed / R. Watanabe, T. Kusuda, H. Yamanishi and K. Yamasaki -- Predicting the profile of intertidal mudflats formed by cross-shore tidal currents / W. Roberts and R.J.S. Whitehouse -- Monitoring of suspended sediment concentration using vessels and remote sensing / J.-Y. Jin, D.-Y. Lee, J.S. Park, K.S. Park and K.D. Yum -- Seasonal variability of sediment erodibility and properties on a macrotidal mudflat, Peterstone Wentlooge, Severn estuary, UK / H.J. Mitchener and D.J. O'Brien -- Observations of long and short term variations in the bed elevation of a macro-tidal mudflat / M.C. Christie, K.R. Dyer and P. Turner -- Influence of salinity, bottom topography, and tides on locations of estuarine turbidity maxima in northern San Francisco Bay / D.H. Schoellhamer -- Boundary layer effects due to suspended sediment in the Amazon River Estuary / S.B. Vinzon and A.J. Mehta -- Modeling mechanisms for the stability of the turbidity maximum in the Gironde estuary, France / A. Sottolichio, P. Le Hir and P. Castaing -- The role of fecal pellets in sediment settling at an intertidal mudflat, the Danish Wadden Sea / T.J. Andersen -- Parameters affecting mud floc size on a seasonal time scale : the impact of a phytoplankton bloom in the Dollard estuary, The Netherlands / W.T.B. van der Lee -- Salt marsh processes along the coast of Friesland, the Netherlands / B.M. Janssen-Stelder -- Prediction of contaminated sediment transport in the Maurice River-Union Lake, New Jersey, USA / E.J. Hayter and R. Gu -- Entrance flow control to reduce siltation in tidal basins / T.J. Smith, R. Kirby and H. Christiansen -- An examination of mud slurry discharge through pipes / P. Jinchai, J. Jiang and A.J. Mehta -- Beach dynamics related to the Ambalapuzha mudbank along the southwest coast of India / A.C. Narayana, P. Manojkumar and R. Tatavarti.
Ηλεκτρονικό βιβλίο
Keywords: Estuarine sediments -- Congresses; Marine sediments -- Congresses; Sediment transport -- Congresses; Electronic books